The Moral Development Based on Kohlberg\'s Theory among Medical Students - Reza Bidaki; Fatemeh Saghafi; Mohammad Mansouri Majoumard; Mahshid Nadershahbaz; Maryam Hadavi; Mohammad Ali Sajadi; Fariba Sepehri; Hadi Ghazalbash; Adeleh Sahebnasagh (Journal of Social Behavior and Community Health, 2022)
Background: One of the main issues in treating, preserving and promoting the human dignity is caring for patients' satisfaction and preventing harm, maltreatment, or damage to the patient. Therefore, the level of moral development based on Kohlberg's theory was studied among medical students of Rafsanjan University of Medical Sciences. Methods: In the current cross-sectional study, eligible medical students (N=220) of Rafsanjan University of Medical Sciences were enrolled over a 12-months period. Data were collected by demographic checklist and Kohlberg's ethical evolution questionnaires. Data were analyzed using SPSS-20, by Kruskal-Wallis, Mann-Whitney, ANOVA, and t-tests. Results: There were no significant differences in terms of gender, educational level, marital status, and place of residence for decision-making positions and questions. The mean and standard deviation of the scores related to “questions, priority, decision-making position and degree” showed that the highest mean was obtained in “priority” with 17.9 ± 3.6 and the lowest in “degree” with 1. 9 ± 1.09. The frequency and percentage of similar decision-making were reported in the study participants; the highest score was related to the decision-making in position 3 (Adults death wish) with frequency of 94 and percentage of 41.6% and the lowest score was related to position 5 (Patient at the end stage of disease) with frequency of 8 and percentage of 3.5%. None of the indicators of age, sex, marital status, and the level of admission was not significant in this study and cannot be mentioned as a predicator in the stages of moral evolution. Conclusion: Given the importance of discussing ethics as one of the most important modalities of the human and social sciences and its impressive impact on all aspects of human life, it is clear that applying a scientific approach can determine all aspects of the factors that affect the observance of ethical principles.